2018
DOI: 10.1007/s12350-018-1293-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac MRI for the evaluation of oncologic cardiotoxicity

Abstract: Cancer therapeutics-related cardiac dysfunction (CTRCD) is a well-established adverse effect resulting from a number of cancer therapeutics. Newer immunotherapy has been associated with cardiomyopathy and myocarditis making comprehensive imaging useful for early recognition. Cardiac MRI (CMR) offers a comprehensive evaluation to detect CTRCD. Established guidelines for monitoring left ventricular ejection fraction for potential cardiotoxicity have recently incorporated CMR. We will review the utility of CMR in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…MRI is especially valuable to evaluate the pericardium, as several sequences may be helpful for a comprehensive evaluation. Using a short‐tau inversion‐recovery (STIR) sequence on T 2 ‐weighted spin‐echo imaging can demonstrate pericardial fluid and edema of the pericardial layers in inflammatory pericarditis, while tagged cine gradient sequences can detect myocardial involvement in constrictive pericarditis and fibrotic adhesion of the pericardium . Figure demonstrates the MRI presentation of therapy‐related pericarditis in mild and severe cases.…”
Section: Tissue Characterizationmentioning
confidence: 99%
See 4 more Smart Citations
“…MRI is especially valuable to evaluate the pericardium, as several sequences may be helpful for a comprehensive evaluation. Using a short‐tau inversion‐recovery (STIR) sequence on T 2 ‐weighted spin‐echo imaging can demonstrate pericardial fluid and edema of the pericardial layers in inflammatory pericarditis, while tagged cine gradient sequences can detect myocardial involvement in constrictive pericarditis and fibrotic adhesion of the pericardium . Figure demonstrates the MRI presentation of therapy‐related pericarditis in mild and severe cases.…”
Section: Tissue Characterizationmentioning
confidence: 99%
“…Figure demonstrates the MRI presentation of therapy‐related pericarditis in mild and severe cases. Free‐breathing cine imaging can also be used to evaluate ventricular interdependence . Additionally, Mukai‐Yatagai et al demonstrated native and postcontrast T 1 mapping by MRI could be used to estimate ECV and evaluate for myocardial fibrosis following radiation therapy .…”
Section: Tissue Characterizationmentioning
confidence: 99%
See 3 more Smart Citations